Combining YESS and TESSYS techniques during percutaneous transforaminal endoscopic discectomy for multilevel lumbar disc herniation. Issue 28 (July 2018) - He, Shenghua; Sun, Zhitao; Wang, Yeguang; Ma, Dujun; Tan, Weiwei; Lai, Juyi
Abstract : Abstract: The authors retrospectively characterized the clinical outcomes of combining the Yeung endoscopic spine system (YESS) and transforaminal endoscopic surgical system (TESSYS) techniques during percutaneous transforaminal endoscopic discectomy (PTED) to treat multilevel lumbar disc herniation. PTED using both YESS and TESSYS was performed on 52 patients with multilevel lumbar disc herniations who had shown no apparent response to previous conservative treatments. Postsurgical follow-ups were conducted at weeks 1, 26, and 48. Patients' preoperative and postoperative performances were assessed by modified MacNab classification, Japanese Orthopedic Association (JOA) scores, Oswestry disability index (ODI), and visual analog scale (VAS), and compared with 34 and 45 patients who were treated only by YESS and TESSYS, respectively. The postsurgery surgeon-performed assessment showed satisfactory results in 98% of the YESS + TESSYS-treated cases. The average operative time was 116 ± 23 minutes, intraoperative bleeding was 19 ± 12 mL, and bed stay was 3 days. No complications occurred, including infection, nerve injury, or spinal canal hematoma. One week after surgery, the modified MacNab classifications of the patients were excellent in 45, good in 6, fair in 1, and poor in 0 (98% were excellent or good). JOA, ODI, and VAS scores for low back pain significantly improved relative to the preoperative assessment ( P < .01) and had remained stable at 26 and 48 weeks. PTED that combined YESS and TESSYS techniques, depending on the predominant type of lumbar disc herniation at individual levels, is safe, minimally invasive, and effective.